Minoan extractions : a photographic journey 2009-2016 : Sissi Archaeological Project - McGuire, Gavin, (Archaeopress Publishing Ltd, 2017)
Archaeologist and award-winning photographer Gavin McGuire brings us on-site to the long-running (and ongoing) Sissi Archaeological Project, Crete, offering unique insights into every key stage of an archaeological excavation and the lives of the archaeologists living and working in often harsh conditions for several weeks at a time.